Investigation of constituents from Cinnamomum camphora (L.) J. Presl and evaluation of their anti-inflammatory properties in lipopolysaccharide-stimulated RAW 264.7 macrophages. (15th July 2018) - Li, Yan-Ru; Fu, Chun-Sheng; Yang, Wen-Jing; Wang, Xiao-Ling; Feng, Dan; Wang, Xiao-Ning; Ren, Dong-Mei; Lou, Hong-Xiang; Shen, Tao
Abstract: Ethnopharmacology relevance: Cinnamomum camphora (L.) J. Presl has been used for the traditional medicine as a therapeutic agent of inflammation-related diseases, including sprains, rheumatic arthritis, abdominal pain, cough and bronchitis, for a long history. The aim of the present study was to illustrate anti-inflammatory substances of C. camphora and their mechanism of action, and to establish the correlations between chemical constituents and traditional uses of this plant. Materials and methods: Chemical constituents were purified by chromatographic methods, and their structures were established based on spectroscopic analysis. Lipopolysaccharide (LPS)-stimulated RAW 264.7 macrophages was adopted for evaluating the anti-inflammatory activity in vitro . The nitric oxide (NO) production assay and nuclear factor kappa B (NF-κB) dual luciferase reporter assay were used to screen anti-inflammatory constituents. The mRNA and protein levels of inflammation-related cytokines and enzymes were determined by real-time reverse transcription-polymerase chain reaction (RT-PCR), immunoblot analysis, and enzyme linked immunosorbent assay (ELISA), respectively. Results: Twenty-five constituents were isolated from the EtOH extract of C. camphora . Eight constituents, covering phenylpropanoid (7 ), lignans (10 and22 ), flavonoids (16 –18 ), coumarin (21 ), and terpenoid (24 ) significantly inhibited LPS-stimulated NO production with maximum inhibition rates (MIRs) of ≥ 80%, and thus were verified to be the anti-inflammatory substances of this ethnomedical plant. (+)-Episesaminone (SMO, 22 ) and 3 S -(+)−9-oxonerolidol (NLD, 24 ) blocked NF-κB activation via inducing IκBα expression. Moreover, SMO and NLD inhibited productions of tumor necrosis factor-α (TNF-α), interleukin-6 (IL-6), and prostaglandin E2 (PGE2), and alleviated increased mRNA and protein levels of inducible nitric oxide synthase (iNOS), cyclooxygenase (COX-2), and matrix metallopeptidase-9 (MMP-9) in LPS-stimulated RAW 264.7 macrophages. Conclusions: The ethnomedical use of C. camphora for the treatment of inflammation-related diseases was attributed to the combined in vitro anti-inflammatory activities of phenylpropanoid, lignan, flavonoid, coumarin, and terpenoid. SMO and NLD were found to be new molecules with in vitro anti-inflammatory activities, which are achieved by inhibiting NF-κB regulated inflammatory response. Graphical abstract: